Plants as pharmaceutical excipients in oral sustained drug delivery systems: A review - Uwah, T O; Akpabio, E I; Effiong, Daniel (Journal of Applied Pharmaceutical Research, 2021)
Plants and their derivatives have contributed immensely to drug development for their application as medicinal agents or as excipients in preparation of new drug delivery systems. Their use keeps increasing by the day. The rich, yet-to-be fully tapped vegetation available in the African sub-region puts it with great potential to be the next global destination as sources for pharmaceutical excipient. This work reviews published articles on plants and derivatives that have been employed so far in modifying drug delivery. Published articles from databases of PubMed, science direct and google scholar were sourced. Obtained manuscripts were screened for relevance to the topic and currency from reading through the abstract and scanning the body of the work. Gums and mucilages as plant derivatives in their natural form or as changed forms have been well investigated for use in controlled drug delivery. Some of these have been as functional in modifying drug release as many commercially employed excipients in drug delivery. Many plants and plant-derived polymers are generally regarded as safe, easily cultivated, show good functionality as drug additives and can be modified to improve on any less desirable property. Taking advantage of these positive factors will open doors for optimal use of these naturally endowed pharmaceutical excipients